PENGARUH KEKERASAN DALAM RUMAH TANGGA (KDRT) TERHADAP TINGKAT KEHARMONISAN DALAM KELUARGA DI KELURAHAN UMBAN SARI KECAMATAN RUMBAI KOTA PEKANBARU - Ramadhan, Rendi Amanda; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Families are two or more individuals who are joined because of blood, marriage relations or rapture and they live in a household, interact with each other in their respective roles, and create also maintain a culture.(Salvicion danan celis, 1989). This research was conducted in Umban Sari Village, Rumbai Sub District, Pekanbaru City. With the formulation of the problem (1) What forms of violence in the household? (2) how is the influence of internal household violence on the level of harmony in the family ?To know the forms of internal household violence and to know the effect of internal household violence on family harmony level, this research is descriptive research with quantitative approach, population in this study overall object studied as much as 36 people then used one of sampling technique saturated sample which represent entire population less than 100 people that is as much as 36 people from year 2016, to collect questionnaires, documentation and observation, based on the results of research can be concluded (1) physical violence against internal household violence is very strong at 82.7%. Psychological violence is strong at 78.0%. Sexual violence is strong at 72.7%. Abandonment of households is strong at 82.1%. Threats to perform acts of coercion or deprivation are very strong by 80.3% with 36 respondents. (2) 98.7%, which means very influential between internal household violence against Harmony in the family, Harmony includes: the love of fellow family members, obedience worship, communication, separation and dialogue between families, high degree of harmony with the percentage of 58.3% of 21 respondents, and answered the low level of harmony 15 respondents with a percentage of 41.6%.Keywords: Violence, Harmony, Family.